Efektifitas Penerapan Aplikasi Google Classroom dalam Pembelajaran Bahasa Indonesia bagi Siswa SMK Negeri di Samarinda - Herianti Herianti; Rahmat Soe'oed; Yusak Hudiyono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
When students are given assignments, sometimes some students do not respond. In fact, teachers have not provided creative learning innovations to students. As a result, the teacher's instructions do not do the task. The study aims to describe the use of Google Classroom applications to attract and train students' skills in writing literacy in Indonesian learning, particularly writing anecdotal texts. The method used in this study is qualitative as for obtaining the data by conducting in-depth interviews using a recording device, then collecting data through a questionnaire to get valid data from students. The subject of this study was a student of class X SMK Negeri Samarinda consisting of the high, medium, and low achievement. The results showed that students are happy to use classroom applications as a medium of learning anecdotal text because they can write creatively and want the application to remain used to share ideas. However, the use of classroom applications also requires a good internet network.